Spectrum of the fractional p-Laplacian in RN and decay estimate for positive solutions of a Schrödinger equation. (April 2020) - Del Pezzo, Leandro M.; Quaas, Alexander
Abstract: In this paper, we prove the existence of unbounded sequence of eigenvalues for the fractional p − Laplacian with weight in R N . We also show a nonexistence result when the weight has positive integral. In addition, we show some qualitative properties of the first eigenfunction including a sharp decay estimate. Finally, we extend the decay result to the positive solutions of a Schrödinger type equation.